Greenland Blocking Promotes Subtropical North Atlantic Spring Blooms. Issue 13 (6th July 2021) - Le, Chengfeng; Chen, Yihui; Lehrter, John C.; Hu, Chuanmin; Bouman, Heather; Cai, Wei‐Jun; Qi, Lin
Abstract: Climate patterns drive broad‐scale patterns of ocean ecosystem productivity. However, the mechanistic connections between regional climate variability and ocean ecosystem responses are not well understood for much of the ocean. By analyzing multi‐decadal atmospheric and oceanic data over the North Atlantic Ocean, we show that the subtropical spring bloom variability is connected to winter Greenland blocking events. The blocking enforces a southward shift of the eddy‐driven jet stream, inducing higher surface westerly winds, causing deeper vertical mixing in the subtropical North Atlantic Ocean in winter and promotes larger spring blooms. These findings reveal the physical mechanisms connecting a predominant climate variability mode in the Arctic with variability in the subtropical spring bloom and highlight the importance of ocean‐atmosphere coupling in shaping the response of oceanic ecosystems to climate variability. Our results also imply a potential teleconnection between rapid Arctic warming over Greenland and phytoplankton variability in the subtropical North Atlantic. Plain Language Summary: Due to the pivotal role of phytoplankton in food webs and the biological pump, it is important to understand how climate change may affects patterns of phytoplankton biomass. Although previous research has examined the relationship between the chlorophyll a concentration anomaly and descriptive climatic indices, the physical and dynamical process underlying the mechanisms remain unclear, particularly the role of large‐scale atmospheric circulation processes. Given that the regional climate mode is dominated by large‐scale atmospheric circulation anomalies, resolving this scientific question helps to clarify the mechanisms behind the interaction between climatic dynamics and the oceanic ecosystem under the current climate conditions. Furthermore, such an analysis helps to project future phytoplankton responses to changing climate. Here, we explored the linkage between atmospheric dynamics and phytoplankton variability in the North Atlantic. The results show that winter upper‐level atmospheric circulation anomalies over Greenland largely control the spring phytoplankton bloom in the subtropical North Atlantic. This linkage not only clarifies the mechanism between climate dynamics and phytoplankton variability, but also shows an exception to the widely accepted paradigm that global warming would cause declines in subtropical phytoplankton. Key Points: Discovered a connection between high‐latitude atmospheric dynamics and subtropical phytoplankton bloom variability in the North Atlantic Revealed the physical and dynamical process linking large‐scale atmospheric dynamics to oceanic ecosystems over the North Atlantic Posed a new conceptual model connecting high‐latitude atmospheric dynamics and subtropical phytoplankton variability in North Atlantic